Reassessing changes in diurnal temperature range: A new data set and characterization of data biases. Issue 10 (17th May 2016) - Thorne, P. W.; Menne, M. J.; Williams, C. N.; Rennie, J. J.; Lawrimore, J. H.; Vose, R. S.; Peterson, T. C.; Durre, I.; Davy, R.; Esau, I.; Klein‐Tank, A. M. G.; Merlone, A.
Abstract: It has been a decade since changes in diurnal temperature range (DTR) globally have been assessed in a stand‐alone data analysis. The present study takes advantage of substantively improved basic data holdings arising from the International Surface Temperature Initiative's databank effort and applies the National Centers for Environmental Information's automated pairwise homogeneity assessment algorithm to reassess DTR records. It is found that breakpoints are more prevalent in DTR than other temperature elements and that the resulting adjustments have a broader distribution. This strongly implies that there is an overarching tendency, across the global meteorological networks, for nonclimatic artifacts to impart either random or anticorrelated rather than correlated biases in maximum and minimum temperature series. Future homogenization efforts would likely benefit from simultaneous consideration of DTR and maximum and minimum temperatures, in addition to average temperatures. Estimates of change in DTR are relatively insensitive to whether adjustments are calculated directly or inferred from adjustments returned for the maximum and minimum temperature series. The homogenized series exhibit a reduction in DTR since the midtwentieth century globally (−0.044 K/decade). Adjustments serve to approximately halve the long‐term global reduction in DTR in the basic "raw" data. Most of the estimated DTR reduction occurred over 1960–1980. In several regions DTR has apparently increased over 1979–2012, while globally it has exhibited very little change (−0.016 K/decade). Estimated changes in DTR are an order of magnitude smaller than in maximum and minimum temperatures, which have both been increasing rapidly on multidecadal timescales (0.186 K/decade and 0.236 K/decade, respectively, since the midtwentieth century). Key Points: Breakpoints are more prevalent in DTR than other temperature elements DTR has decreased since the early twentieth century, but decrease is not linear Effects of homogenization alter many details of global and regional changes